Comment on IWGDF ulcer prevention guidelines. Issue 1 (24th July 2020) - Nickerson, David Scott; Barrett, Stephen L.
Abstract : The IWGDF 2019 Updated Guidelines for prevention of foot ulcers in diabetes advise that nerve decompression surgery not be considered. This nerve decompression option has similar scientific supporting evidence to other surgeries which are recommended. The sanction ignores a large body of non‐Level 1 evidence demonstrating various beneficial outcomes of ND including pain relief, DFU prevention, and protection from recurrence and amputation.